Capacitive Power Transfer System With Double T-Type Resonant Network for Mobile Devices Charging/Supply - Liu, Zhe; Su, Yu-Gang; Zhao, Yu-Ming; Hu, Aiguo Patrick; Dai, Xin (IEEE transactions on power electronics, 2022)
In the applications of wireless power transfer for mobile devices, the pick-up of the wireless power transfer system often needs to be moved in and moved out. A sudden change in the system structure will cause high transient voltages or currents, which could damage the power electronic device of the capacitive power transfer (CPT). In addition, the standby power of the system will be too high to work after removing the pick-up. A CPT system with double T-type resonant networks has been proposed to address these problems. The steady-state models of the system without the pick-up and normal state conditions of it are established. The relationships between the resonant network parameters are analyzed, and a systematic circuit parameter design method is provided. The proposed CPT topology and the parameter design method have been verified by simulation and experiment. The system not only achieved self-protection under severe load change but also entered standby mode automatically after the pick-up was moved out. Besides, the system is restored to the normal state condition when the pick-up is moved in without additional detection and control circuitry.